Pengaruh Attitude, Subjective Norm, dan Perceived Behavioral Control terhadap Repurchase Intention E-Money - ARIYANTO, DEBBY (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract The development of information technology has huge effect on human life. Changes in transactions became one of thing that are easily observed. This study aims to analyze and discuss the influence of attitude, subjective norm, and perceived behavioral control to e-money repurchase intention. This type of this research is conclusive with quantitative approach. Sampling method is non probability with sampling technique using sinmple rendom sampling to all Indonesian who used e-money. This research used 210 respondents as sample. Data collection technique used in this study is questionnaire, documentation, and interview. This study used Multiple Regression Analysis as analysis techniques with IBM SPSS 24 program. The result of this study indicate that attitude, subjective norm, and perceived behavioral control has positive effect to e-money repurchase intention. Keywords: attitude, subjective norm, perceived behavioral control, repurchase intention, e-money